La desnutrición y su incidencia en el crecimiento y desarrollo intelectual en los niños (as) menores de 5 años que acuden a la fundación Rotary “quevedo”, durante el segundo semestre del 2014 - Castro Choez, Marlene Beatríz (2015)
This research entitled: of malnutrition in children under five years and its relationship with stunting, intellectual development attending the Rotary "Quevedo" Foundation during the second half of 2014, to determine the factors that are causing malnutrition also design educational programs to train mothers on this social problem. Types of bibliographical and documentary research that led to gather information regarding malnutrition was used in the study, field research helped to know the current situation regarding the disease in the Rotary "Quevedo" Foundation also was applied as instruments the survey consented to determine the sample to a segment of 332 mothers of children under 5 years. The results gathered in the investigation establishes that there is a 87% of mothers who consider feeding their children are low in nutrients, generated little training or guidance on proper nutrition, this ultimately led to propose an alternative for provide educational tools that optimize knowledge of mothers about the importance of feeding children with the necessary nutrients to improve their growth and intellectual development. Keywords: malnutrition, younger children, growth and intellectual development